Serial Measurement of Interleukin-6 Enhances Chance to Exclude Early-Onset Sepsis in Very Preterm Infants - Berka, Ivan; Korček, Peter; Straňák, Zbyněk (Clinical pediatrics, 2023)
The aim of this retrospective study was to evaluate the reliability of peak interleukin-6 (IL-6) level within 24 hours after delivery as a predictor for early-onset sepsis (EOS) in very preterm neonates. Interleukin-6 was assessed at 2 hours and at 12 to 24 hours after delivery. The highest level was considered a peak value. The definition of EOS was based on positive blood culture and clinical signs of infection or negative blood culture, clinical signs of infection, and C-reactive protein >10 mg/L. Among 445 enrolled infants, 53 developed EOS. A peak IL-6 level of more than 200 ng/L had a sensitivity of 89% and specificity of 77% for the presence of EOS. The negative predictive value was 98%. Receiver operating characteristics curve had area under the curve of 0.92. Peak IL-6 is a reliable marker of systemic inflammatory response and might be useful to exclude EOS within the first 24 hours.
Keywords: Reproducibility of Results; C-Reactive Protein; Sepsis; interleukin-6; reprodukovatelnost výsledků; Retrospective Studies; Interleukin-6; C-reaktivní protein; nemoci nedonošenců; Infant, Premature, Diseases; Infant, Newborn; novorozenec; retrospektivní studie; Humans; novorozenecká sepse; biologické markery; sepse; Infant, Premature; Neonatal Sepsis; Biomarkers; novorozenec nedonošený; lidé